An analysis of multi-GNSS observations tracked by recent Android smartphones and smartphone-only relative positioning results - Paziewski, Jacek; Fortunato, Marco; Mazzoni, Augusto; Odolinski, Robert (Measurement : journal of the International Measurement Confederation, 2021)
[Display omitted] •Smartphone collaborative positioning with fixed ambiguities provides a precise cm-level solution.•C/N0s of smartphone GNSS show discernible differences among constellations and signal bands.•There are important divergences in GNSS observation noise among smartphones.•GNSS phase observations of selected smartphones are subject to unexpected drifts.•GNSS phase noise may be efficaciously assessed with the variometric approach. In this study we assess the quality of multi-GNSS observations of recent Android smartphones. The results reveal a significant drop of smartphone carrier-to-noise density ratio (C/N0) with respect to geodetic receivers, and discernible differences among constellations and frequency bands. We show that the higher the elevation of the satellite, the larger discrepancy in C/N0 between the geodetic receivers and smartphones. Thus we show that a C/N0 weighting scheme may be superior to the elevation dependent one usually adopted for GNSS observations. We also discover that smartphone code pseudoranges are noisier by about one order of magnitude as compared to geodetic receivers, and that the code signals on L5 and E5a outperform those on L1 and E1, respectively. It is shown that smartphone phase observations are contaminated by the effects that can destroy the integer property and time-constancy of the ambiguities. There are long term drifts detected for GPS L5, Galileo E1, E5a and BDS B1 phase observations of Huawei P30. We highlight competitive phase noise characteristics for the Xiaomi Mi 8 when compared to the geodetic receivers. We also reveal a poor quality of other than GPS L1 phase signals for the Huawei P30 smartphones related to the unexpected drifts of the observations. Finally, the positioning experiment proves that it is feasible to obtain a precise cm-level solution of a smartphone to smartphone relative positioning with fixed integer ambiguities.